Design and test of fault monitoring system for corn precision planter - Jiangtao, Qi; Honglei, Jia; Yang, Li; Haibo, Yu; Xinhui, Liu; Yubin, Lan; Xianzhen, Feng; Yongxi, Yang (International Journal of Agricultural and Biological Engineering, 2015)
With the growing demand and working complexity of corn precision planter, it becomes more important to monitor the working performance through intelligent systems. A new fault monitoring system for corn precision planters was designed and tested. This system consisted of the information acquisition module, controller module, alarm module, input module and display module. A capacitive sensor was utilized to monitor the seed flow without changing the track of a precision planter. This system can monitor the whole sowing process of a seed-metering device in real-time. The sowing status, fault type and fault location can be displayed on liquid crystal display (LCD). Warning light on the LCD reminds the operator of abnormal conditions. Bench tests and field tests showed that the minimum monitoring accuracies of missing sowing and total sowing number were 92.11% and 94.28%, respectively, and the seed level sensor and the opener sensor worked well. This system can accurately prompt the seed-metering mechanism in real-time. Keywords: corn, precision planter, fault monitoring system, precision agriculture, capacitive sensor, missing sowing DOI: 10.3965/j.ijabe.20150806.1968 Citation: Qi J T, Jia H L, Li Y, Yu H B, Liu X H, Lan Y B, et al. Design and test of fault monitoring system for corn precision planter. Int J Agric & Biol Eng, 2015; 8(6): 13－19.